Factoring Predicate Argument and Scope Semantics: Underspecified Semantics with LTAG - Kallmeyer, Laura; Joshi, Aravind (Proceedings of the Amsterdam Colloquium, 1999)
This paper proposes a compositional semantics for lexicalized treeadjoining grammar (LTAG) . Tree-local multicomponent derivations allow separation of the semantic contribution of a lexical item into one component contributing to the predicate argument structure and a second component contributing to scope semantics. Based on this idea a syntax-semantics interface is presented where the compositional semantics depends only on the derivation structure. It is shown that the derivation structure (and indirectly the locality of derivations) allows an appropriate amount of underspecification. This is illustrated by investigating underspecified representations for quantifier scope ambiguitites and related phenomena such as adjunct scope and island constraints.